MOBILE APPS IN UZBEKISTAN MAKE A SIGNIFICANT CONTRIBUTION TO THE DEVELOPMENT OF TOURISM - Khodjaeva Mavluda Sabirovna; Azamat Bozorov; Alimjon Dadamuxamedov (International Engineering Journal For Research & Development, 2020)
In subsequent years, as one of the strategic sectors contributing to the rapid development of regions, increasing income and living standards of the population, as well as increasing investment attractiveness, measures are being taken to develop tourism in Uzbekistan. Modern information technologies make a significant contribution to the development of pilgrim tourism. Advertising of travel online services in pilgrim tourism currently does not allow for the automation of travel agency work without creating an effective website. This article is devoted to the analysis of Internet technologies aimed at improving the tourism industry. The practical significance of the article lies in the use of modern information and communication technologies that support activities in the field of pilgrim tourism in the region. Ancient architectural and historical monuments of our country are of great interest to the world community. Especially in recent years, thanks to the ongoing work to develop tourism, the number of foreign tourists is growing. In addition, new areas such as ecotourism, gastronomic tourism, agritourism, sports tourism will be developed for tourists, traditional cultural and educational events, festivals and competitions will be held. Along with ancient monuments, shrines, monuments of history and culture, efforts in this direction in our country, which attracts tourists with its unique culture and traditions, picturesque nature and picturesque corners, play an important role in the further development of the tourism industry and infrastructure. This is evidenced by the fact that the World Travel and Tourism Council (WTTC) in the study "Economic performance of the travel and tourism industry" noted that our country is among the five fastest growing countries in the tourism industry.